2014
DOI: 10.1017/jfm.2013.658
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of aero-optical properties of subsonic turbulent boundary layers

Abstract: This paper gives the most-complete characterization to date of the optical aberrations imposed on a laser beam propagated through a subsonic, compressible, turbulent boundary layer in a zero-pressure gradient environment, over a range of boundarylayer thicknesses, oblique propagation angles and Mach numbers. This characterization is based on optical measurements using optical-wavefront-sensing instruments that have only become available in the last decade. The optical characterization includes and discusses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
113
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(142 citation statements)
references
References 56 publications
(88 reference statements)
15
113
0
Order By: Relevance
“…For both the Caltech wavefront data obtained at Reθ = 1,700 the convective velocity was found to be 0.83U ∞ using the correlation of the two beams, a value which is consistent with wavefront measurements obtained previously at higher Reynolds numbers [9,14]. For wavefronts obtained in the Notre Dame facility, the convective velocity was found to be 0.82U ∞, which is also consistent with previous measurements in this facility at higher Reynolds numbers.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…For both the Caltech wavefront data obtained at Reθ = 1,700 the convective velocity was found to be 0.83U ∞ using the correlation of the two beams, a value which is consistent with wavefront measurements obtained previously at higher Reynolds numbers [9,14]. For wavefronts obtained in the Notre Dame facility, the convective velocity was found to be 0.82U ∞, which is also consistent with previous measurements in this facility at higher Reynolds numbers.…”
Section: Resultssupporting
confidence: 89%
“…The peaks for all measured spectra are at St δ = 1.0, independent of Reynolds number. In [14] it was shown that using Kolmogorov-like arguments for the inertial range, the deflection angle amplitude spectrum at large frequencies should behave as ~f (−2/3) . This spectra behavior is Smith et al…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations